Beauveria bassiana assisted remediation of chromium and indanthane blue. Issue 4 (August 2021) - Gola, Deepak; Tyagi, Pankaj Kumar; Chauhan, Nitin; Malik, Anushree; Srivastava, Sunil Kumar
Abstract: The presence of toxic pollutants in wastewater is a matter of great concern, posing risk to environment and health. Generally, dyes and heavy metals are concomitant pollutants of wastewaters, associated with multiple diseases in humans. Various physical and chemical approaches of removing these contaminants have been in use, however biological approach, utilizing microorganisms has been identified as an advantageous option. The present study utilized the potential of fungus, Beauveria bassiana for the removal of Chromium (Cr) and Indanthane blue, individually and simultaneously. Results showed that maximum Cr removal of 61% was observed at 30 mg L −1 with 3.8 mg g −1 of specific metal uptake. Further, 99.6% removal of dye (Indanthane blue) was observed at 200 mg L − 1 of initial dye concentration. The results of simultaneous removal of Cr and dye mixture highlighted the higher potential of B. bassiana for dye removal in comparison to Cr uptake. Moreover, the temperature of 30 °C with pH value of 7, accounts for maximum removal efficacy by B. bassiana . The analytical techniques, such as Atomic force microscopy (AFM) and Transmission electron microscopy high-angle annular dark field (TEM HAADF) were employed to study the morphological characteristics of B. bassiana in presence of Cr and dye. AFM highlighted the increase in surface roughness of B. Bassiana cells, further TEM HAADF clearly indicated the localization of heavy metals within the cells of B. bassiana . Graphical Abstract: ga1 Highlights: B. bassiana was used for the removal of dye (Indanthane blue) and metal (Chromium). Efficient removal was obtained individually (dye and metal) as well as dye +metal mixture. AFM and TEM-HAADF were used for morphological characterization of B. bassiana. TEM-HAADF indicated localization of heavy metals within B. bassiana cells.